Book Review: Cheating in School: What We Know and What We can Do - Fachruddin, Fuad (Yayasan Sukma Bangsa, 2017)
Title: CHEATING IN SCHOOL: What We Know and What We can DoAuthors: Stephen F. Davis; Patrick F. Drinan; Tricia Bertram GallantPublication: J. Wiley & Sons, UK, 2009Pages: 240 pages